Cultural and educational leisure activities in nules of Ukraine - KOVALCHUK, Tamara; MELNICHUK, Tetyana (Journal of Education, Technology and Computer Science, 2013)
Cultural and educational work in NULES of Ukraine has fruitful influenceon the formation of future social teachers’ preparedness to deal with leisure activity.The favorable conditions are created at the University with the purpose ofindividual and professional qualities improvement; theatrical, vocal and musicalgifts perfection and physical development.